Controls on beach-ridge formation in a low-energy polar environment and implications for luminescence geochronology - Jacinda O'Connor; Richard Jones; Jan-Hendrik May; Juliet Sefton; Andrew Mackintosh; Kieran O'Gorman; Felix Lauer; Levan Tielidze; Corey Port; Duanne White; Lu Li (Marine Geology, 2026)

Maternal mycoestrogen exposure in relation to timing of birth and placental corticotropin releasing hormone concentrations in a U.S. pregnancy cohort - Alyssa Juenke; Megan C. Hansel; Carolyn W. Kinkade; Anita Brinker; Maria Bowman; Roger Smith; Richard K. Miller; Jessica Brunner; Brian Buckley; Thomas G. O’Connor; Lauren M. Aleksunes; Zorimar Rivera- Núñez; et al. (Reproductive Toxicology, 2026)

Associations of Placental Oxidative Stress with Exposure to Gestational Air Pollution: Evidence from the UPSIDE Cohort - Emily A. Craig; Yan Lin; Yihui Ge; Xiangtian Wang; Otgondelger Enkhtaivan; Don K. Harrington; Richard K. Miller; Susan K. Murphy; Sally W. Thurston; Philip K. Hopke; Emily S. Barrett; Thomas G. O'Connor; et al. (Environmental Research, 2026)

New evidence for the Clactonian-Acheulean succession during MIS 11 from Devereux's Pit, Suffolk, UK - Rob Davis; Marcus Hatch; Simon G. Lewis; Claire Lucas; Simon O'Connor; Claire R.E. Harris; Joshua T. Hogue; Dylan Jones; Ellie Nelson; Simon A. Parfitt; Richard C. Preece; Kathryn M. Price; et al. (Quaternary Science Reviews, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Development and Evaluation of Foundational Cancer Science Graduate Courses in the Evolving Landscape of Cancer Research - Eugene Kandel; Michael Nemeth; Richard O’Connor; Stephanie Tzetzo; AnneMarie W. Block; Spencer Rosario; Tatiana Shaurova; Mukund Seshadri; Pamela A. Hershberger (Journal of Cancer Education, 2026)
Roswell Park is a free-standing Comprehensive Cancer Center in Buffalo, New York and serves as the academic home to a doctoral program in Cancer Sciences. To meet the evolving cancer research landscape, we developed and implemented a series of sequential Integrated Cancer Sciences (ICS-I, ICS-II, and ICS-III) courses that provide a strong, multi-disciplinary foundational knowledge to graduate trainees, regardless of their eventual specialization. These courses span the entire spectrum of cancer research from basic biology to population science/epidemiology, cancer therapeutics, and clinical oncology and were intentionally developed to prepare trainees for diverse careers in cancer research. The engagement and participation of basic, population science, and clinical faculty was integral for successful implementation of these courses. Survey responses were collected from students who had completed the ICS courses since 2018 to evaluate course content, depth, and perceived value. Ninety-five percent of respondents felt the depth of course content was appropriate for graduate study. A majority of trainees (74%) felt that the ICS courses significantly expanded their knowledge base beyond their immediate interest area. We continue to assess and update the content of ICS courses to better reflect the growing training needs, especially in emerging technologies such as artificial intelligence (AI).

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Bayesian inference to predict past and future nitrate concentrations - Matt Dumont; Connor Cleary; Richard McDowell (Journal of Contaminant Hydrology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

A comprehensive approach for detecting and locating black carbon in human placentae - Atsuo Chiu; Denise Ivey; Amanda Sanko; Barbara Tisdale; Philip J. Katzman; Thomas G. O’Connor; Kaye Thomas; Tanzy Love; Rogelio Perez-D’Gregorio; Carolyn M. Salafia; Richard K. Miller; Philip K. Hopke (Air Quality, Atmosphere & Health, 2026)

Transcriptomic profiling of wild Atlantic salmon affected with red skin disease (RSD) - Irene Cano; Connor Harvey; Richard Paley; Richard Hill; Mary Buckley; Adele Cobb; Ronny van Aerle; Silvia Soares; Chris Williams (Fish & Shellfish Immunology, 2025)

Prenatal air pollution exposure and placental vasculature development among participants of the UPSIDE cohort study - Shivram Kumar; Carolyn M. Salafia; Ruchit Shah; Theresa Girardi; Richard K. Miller; Sally W. Thurston; Philip K. Hopke; David Skrill; Jessica Brunner; Donald Harrington; Yihui Ge; Yan Lin; et al. (Environmental Research, 2025)

PM2.5 and NO2 exposure during pregnancy and measures of fetal size and attained size at birth - Nafisa Nawal Islam; Sally W. Thurston; Donald Harrington; Yihui Ge; Samuel Weisenthal; Jessica Brunner; Richard K. Miller; Philip K. Hopke; Yan Lin; Emily S. Barrett; Thomas G. O’Connor; Junfeng Zhang; et al. (Air Quality, Atmosphere & Health, 2025)

Effects of 24-h sleep deprivation on whole-body heat exchange in young men during exercise in the heat - Nicholas J. Koetje; Nathalie V. Kirby; Fergus K. O’Connor; Brodie J. Richards; Kristina-Marie T. Janetos; Leonidas G. Ioannou; Glen P. Kenny (European Journal of Applied Physiology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Maternal organophosphate esters and sex steroid hormones in mid-pregnancy - Megan C. Hansel; Katherine A. Lubina; Troy A. Roepke; Pamela Ohman-Strickland; Kurunthachalam Kannan; Christina Wang; Richard K. Miller; Thomas G. O'Connor; Zorimar Rivera-Núñez; Emily S. Barrett (Environmental Research, 2025)

Postglacial Recolonization of the Southern Ocean by Elephant Seals Occurred From Multiple Glacial Refugia - Andrew A. Berg; Megan Askew; Frederik V. Seersholm; Alexander J. F. Verry; A. Rus Hoelzel; Andreanna Welch; Karen Greig; Richard Walter; Michael Knapp; Axel Barlow; Johanna L. A. Paijmans; Jonathan M. Waters; et al. (Global Change Biology, 2025)
The Southern Ocean is warming more rapidly than other parts of our planet. How this region's endemic biodiversity will respond to such changes can be illuminated by studying past events through genetic analyses of time‐series data sets, including historic and fossil remains. Archaeological and subfossil remains show that the southern elephant seal ( Mirounga leonina ) was common along the coasts of Australia and New Zealand in the recent past. This species is now mostly confined to sub‐Antarctic islands and the southern tip of South America. We analyzed ancient seal samples from Australia (Tasmania), New Zealand and the Antarctic mainland to examine how southern elephant seals have responded to a changing climate and anthropogenic pressures during the Holocene. Our analyses show that these seals formed part of a broader Australasian lineage, comprising seals from all sampled locations from the south Pacific sector of the Southern Ocean. Our study demonstrates that southern elephant seal populations have dynamically altered both range and population sizes under climatic and human pressures over surprisingly short evolutionary timeframes for such a large, long‐lived mammal.

Effect of fluid temperature on the relation and agreement between perceptual and physiological strain during simulated work in a hot environment - Fergus K. O'Connor; Brodie J. Richards; Leonidas G. Ioannou; Glen P. Kenny (Journal of Thermal Biology, 2025)

Prenatal exposure to phthalates and phthalate replacements in relation to chorionic plate surface vasculature at delivery - Emily S. Barrett; David Skrill; Elaine Zhou; Sally W. Thurston; Theresa Girardi; Jessica Brunner; Hai-Wei Liang; Richard K. Miller; Carolyn M. Salafia; Thomas G. O'Connor; Jennifer J. Adibi (Science of The Total Environment, 2025)

A Latitudinal Cline in the Taxonomic Structure of Eelgrass Epifaunal Communities is Associated With Plant Genetic Diversity - Collin P. Gross; J. Emmett Duffy; Kevin A. Hovel; Pamela L. Reynolds; Christoffer Boström; Katharyn E. Boyer; Mathieu Cusson; Johan Eklöf; Aschwin H. Engelen; Britas Klemens Eriksson; F. Joel Fodrie; John N. Griffin; et al. (Global Ecology and Biogeography, 2024)
Aim Biogenic structural complexity increases mobile animal richness and abundance at local, regional and global scales, yet animal taxa vary in their response to complexity. When these taxa also vary functionally, habitat structures favouring certain taxa may have consequences for ecosystem function. We characterised global patterns of epifaunal invertebrates in eelgrass ( Zostera marina ) beds that varied in structural and genetic composition. Location North America, Europe and Asia. Time Period 2014. Major Taxa Studied Peracarid crustaceans and gastropod molluscs. Methods We sampled epifaunal invertebrate communities in 49 eelgrass beds across 37° latitude in two ocean basins concurrently with measurements of eelgrass genetic diversity, structural complexity and other abiotic and biotic environmental variables. We examined how species richness, abundance and community composition varied with latitude and environmental predictors using a random forest approach. We also examined how functional trait composition varied along with community structure. Results Total species richness decreased with latitude, but this was accompanied by a taxonomic shift in dominance from peracarid crustaceans to gastropods, which exhibited different sets of functional traits. Greater eelgrass genetic diversity was strongly correlated with both richness and abundance of peracarids, but less so for gastropods. Main Conclusions Our results add to a growing body of literature that suggests genetic variation in plant traits influences their associated faunal assemblages via habitat structure. Because peracarids and gastropods exhibited distinct functional traits, our results suggest a tentative indirect link between broad‐scale variation in plant genetic diversity and ecosystem function.

Trends in population structure of Patagonian toothfish over 25 years of fishery exploitation at South Georgia - José Abreu; Philip R. Hollyman; José C. Xavier; Connor C.G. Bamford; Richard A. Phillips; Martin A. Collins (Fisheries Research, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Sixty years of research on bracken fern (Pteridium spp.) toxins: Environmental exposure, health risks and recommendations for bracken fern control - Rui M. Gil da Costa; Andrew Povey; Beatriz Medeiros-Fonseca; Carmel Ramwell; Connie O'Driscoll; David Williams; Hans Chr B. Hansen; Lars Holm Rasmussen; Mary T. Fletcher; Peter O'Connor; Richard H.W. Bradshaw; Roderick Robinson; et al. (Environmental Research, 2024)

Systemic oxidative stress levels during the course of pregnancy: Associations with exposure to air pollutants - Xiangtian Wang; Yan Lin; Yihui Ge; Emily Craig; Xiaodong Liu; Richard K. Miller; Sally W. Thurston; Jessica Brunner; Emily S. Barrett; Thomas G. O'Connor; David Q. Rich; Junfeng (Jim) Zhang (Environmental Pollution, 2024)

Intergenerational toxicity of 17α-ethinylestradiol (EE2): Effects of parental exposure on early larval development and transcriptomic profiles in the Sydney rock oyster, Saccostrea glomerata - Rafiquel Islam; Richard Man Kit Yu; Wayne A. O’Connor; Xiao Lin; Keng Po Lai; Frederic D.L. Leusch; Geoff R. MacFarlane (Journal of Hazardous Materials, 2024)

Population dynamics of the Lyme disease bacterium, Borrelia burgdorferi , during rapid range expansion in New York State - Zachary J. Oppler; Melissa A. Prusinski; Kayleigh R. O'Keeffe; Patrick Pearson; Stephen M. Rich; Richard C. Falco; Vanessa Vinci; Collin O'Connor; Jamie Haight; P. Bryon Backenson; Dustin Brisson (Molecular Ecology, 2024)
Recent changes in climate and human land‐use have resulted in alterations of the geographic range of many species, including human pathogens. Geographic range expansion and population growth of human pathogens increase human disease risk. Relatively little empirical work has investigated the impact of range changes on within‐population variability, a contributor to both colonization success and adaptive potential, during the precise time in which populations are colonized. This is likely due to the difficulties of collecting appropriate natural samples during the dynamic phase of migration and colonization. We systematically collected blacklegged ticks ( Ixodes scapularis ) across New York State (NY), USA, between 2006 and 2019, a time period coinciding with a rapid range expansion of ticks and their associated pathogens including Borrelia burgdorferi , the etiological agent of Lyme disease. These samples provide a unique opportunity to investigate the population dynamics of human pathogens as they expand into novel territory. We observed that founder effects were short‐lived, as gene flow from long‐established populations brought almost all B. burgdorferi lineages to newly colonized populations within just a few years of colonization. By 7 years post‐colonization, B. burgdorferi lineage frequency distributions were indistinguishable from long‐established sites, indicating that local B. burgdorferi populations experience similar selective pressures despite geographic separation. The B. burgdorferi lineage dynamics elucidate the processes underlying the range expansion and demonstrate that migration into, and selection within, newly colonized sites operate on different time scales.

A longitudinal behavioral analysis of aquarium whale sharks (Rhincodon typus): insights into anticipatory cues, individual variation, and social interaction - Connor G. Gallimore; Celeste Walton; Richard Nugent; Maury Fradkin; Laurie Poppell; Christian Schreiber; Christopher Coco; Matthew Grober; Bruce Carlson; Alistair D. M. Dove; Michael P. Black (Frontiers in Marine Science, 2024)
Rhincodon typus , or the whale shark, is the largest extant fish in the world and is classified as endangered on the IUCN’s Red List. Due to their enormous size and conservation status, whale sharks are rarely housed in aquaria. Here we present a behavioral analysis culminating from a large effort by 89 observers from 2008–2012 to study four R. typus (ID codes: AL, TA, TR, YU) longitudinally in an aquarium setting. We found that relatively simple behavioral metrics such as swim speed, depth occupation, swimming direction, and lead-follow interactions demonstrated R. typus individual variation and responses to habitat changes. All sharks displayed increased swim speeds 30-minutes before regimented feed times, when there was scent of food being fed to other animals in the habitat. Consistently in the habitat, one male shark (YU) was recorded swimming more at depth, faster, almost exclusively clockwise, and engaged in fewer close proximity interactions with others than expected by chance. In contrast, a larger female shark (AL) was observed swimming the slowest, at the surface more than others, led other sharks more than she followed, and had strong lead-follow interactions with another shark of the opposite sex (TA). TA and TR did not differ from each other in depth profiles or speed, but did differ in their proclivity to lead or follow. Depth preferences and lead-follow interactions suggest some partitioning of the habitat and the possibility of social hierarchy in this species. These results represent the first longitudinal behavioral analysis of aquarium R. typus , offering meaningful similarities and contrasts to field observations.

Associations between mycoestrogen exposure and sex steroid hormone concentrations in maternal serum and cord blood in the UPSIDE pregnancy cohort - Carolyn W. Kinkade; Lauren M. Aleksunes; Anita Brinker; Brian Buckley; Jessica Brunner; Christina Wang; Richard K. Miller; Thomas G. O'Connor; Zorimar Rivera-Núñez; Emily S. Barrett (International Journal of Hygiene and Environmental Health, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Participation in collaborative fisheries research improves the perceptions of recreational anglers towards marine protected areas - Erin M. Johnston; Grant T. Waltz; Rosamaria Kosaka; Ellie M. Brauer; Shelby L. Ziegler; Erica T. Jarvis Mason; Hunter S. Glanz; Lauren Zaragoza; Allison N. Kellum; Rachel O. Brooks; Brice X. Semmens; Christopher J. Honeyman; et al. (Frontiers in Marine Science, 2024)
Collaborative fisheries research programs engage stakeholders in data collection efforts, often with the benefit of increasing transparency about the status and management of natural resources. These programs are particularly important in marine systems, where management of recreational and commercial fisheries have historically been contentious. One such program is the California Collaborative Fisheries Research Program (CCFRP), which was designed in 2006 to engage recreational anglers in the scientific process and evaluate the efficacy of California’s network of marine protected areas. CCFRP began on the Central Coast of California and expanded statewide in 2017 to include six partner institutions in three regions: Northern, Central, and Southern California. To date, over 2,000 volunteer anglers have participated in the program, with many anglers volunteering for multiple years. However, the impacts of outreach, education, and collaborative research on those anglers at the statewide scale are currently unknown. Thus, the objective of the current study was to survey the statewide pool of volunteer anglers to assess the degree to which participation in CCFRP has influenced angler perceptions of MPAs, fisheries management, and conservation. We received 259 completed surveys out of a pool of 1,386 active anglers, equating to an 18.7% response rate. Participation in CCFRP resulted in a significant, positive impact on anglers’ attitudes towards MPAs in California across all regions. Anglers who participated in six or more CCFRP fishing trips had a more positive perception of MPAs than those who participated in fewer trips. Volunteer anglers across all regions perceived that they caught larger fishes, a higher abundance of fishes, and a greater diversity of species inside MPAs, consistent with the ecological findings of the program. These results highlight the benefits of involving community members in collaborative scientific research. Collaboration between researchers and the broader community increases transparency and trust between stakeholders, and results in greater understanding of natural resource dynamics, ultimately producing better management outcomes.

Corrigendum to “Mechanisms of water-rock interaction and implications for remediating flooded mine workings elucidated from environmental tracers, stable isotopes, and rare earth elements” - Connor P. Newman; Katherine Walton-Day; Robert L. Runkel; Richard T. Wilkin (Applied Geochemistry, 2023)

Modelling wine grapevines for autonomous robotic cane pruning - Henry Williams; David Smith; Jalil Shahabi; Trevor Gee; Mahla Nejati; Ben McGuinness; Kale Black; Jonathan Tobias; Rahul Jangali; Hin Lim; Mike Duke; Oliver Bachelor; et al. (Biosystems Engineering, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Mechanisms of water-rock interaction and implications for remediating flooded mine workings elucidated from environmental tracers, stable isotopes, and rare earth elements - Connor P. Newman; Katherine Walton-Day; Robert L. Runkel; Richard T. Wilkin (Applied Geochemistry, 2023)

Observing relationships between sediment-laden meltwater plumes, glacial runoff and a retreating terminus at Blomstrandbreen, Svalbard - Guy D. Tallentire; Connor J. Shiggins; Lauren D. Rawlins; Jeffrey Evans; Richard Hodgkins (International Journal of Remote Sensing, 2023)

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

Logistical considerations and challenges in deploying virtual biomethane pipelines to serve on-farm biogas plants - Dónal Ó Céileachair; Seán O'Callaghan; David M. Wall; David Goulding; Declan O'Connor; Jerry D. Murphy; Richard O'Shea (Journal of Cleaner Production, 2023)

Digestion of human milk processed by high pressure processing and Holder pasteurization using a dynamic in vitro model of the preterm infant - Michael A. Pitino; Sharon Unger; Alain Doyen; Yves Pouliot; Akash Kothari; Mélanie Sergius-Ronot; Richard P. Bazinet; Debbie Stone; Deborah L. O'Connor (Food Chemistry, 2023)

Protective role of the placental efflux transporter BCRP/ABCG2 in the relationship between prenatal cadmium exposure, placenta weight, and size at birth - Emily S. Barrett; Zorimar Rivera-Núñez; Kylie Getz; Pamela Ohman-Strickland; Ranran Zhang; Danielle Kozlosky; Cathleen L. Doherty; Brian T. Buckley; Jessica Brunner; Richard K. Miller; Thomas G. O'Connor; Lauren M. Aleksunes (Environmental Research, 2023)

Neurobiochemical, Peptidomic, and Bioinformatic Approaches to Characterize Tauopathy Peptidome Biomarker Candidates in Experimental Mouse Model of Traumatic Brain Injury - Hamad Yadikar; Connor Johnson; Niko Pafundi; Lynn Nguyen; Milin Kurup; Isabel Torres; Albandery Al-Enezy; Zhihui Yang; Richard Yost; Firas H. Kobeissy; Kevin K. W. Wang (Molecular Neurobiology, 2023)

Towards European automatic bioaerosol monitoring: Comparison of 9 automatic pollen observational instruments with classic Hirst-type traps - José M. Maya-Manzano; Fiona Tummon; Reto Abt; Nathan Allan; Landon Bunderson; Bernard Clot; Benoît Crouzy; Gintautas Daunys; Sophie Erb; Mónica Gonzalez-Alonso; Elias Graf; Łukasz Grewling; et al. (Science of The Total Environment, 2023)

Prenatal perfluoroalkyl substances exposure and maternal sex steroid hormones across pregnancy - Zorimar Rivera-Núñez; Carolyn W. Kinkade; Leena Khoury; Jessica Brunner; Hannah Murphy; Christina Wang; Kurunthachalam Kannan; Richard K. Miller; Thomas G. O'Connor; Emily S. Barrett (Environmental Research, 2023)

Decision times in orthographic processing: a cross-linguistic study - Marika Mauti; Chiara Valeria Marinelli; Richard J. O’Connor; Pierluigi Zoccolotti; Marialuisa Martelli (Experimental Brain Research, 2023)
Reading comparisons across transparent and opaque orthographies indicate critical differences that may reveal the mechanisms involved in orthographic decoding across orthographies. Here, we address the role of criterion and speed of processing in accounting for performance differences across languages. We used binary tasks involving orthographic (words–pseudowords), and non-orthographic materials (female–male faces), and analyzed results based on Ratcliff’s Diffusion model. In the first study, 29 English and 28 Italian university students were given a lexical decision test. English observers made more errors than Italian observers while showing generally similar reaction times. In terms of the diffusion model, the two groups differed in the decision criterion: English observers used a lower criterion. There was no overall cross-linguistic difference in processing speed, but English observers showed lower values for words (and a smaller lexicality effect) than Italians. In the second study, participants were given a face gender judgment test. Female faces were identified slower than the male ones with no language group differences. In terms of the diffusion model, there was no difference between groups in drift rate and boundary separation. Overall, the new main finding concerns a difference in decision criterion limited to the orthographic task: English individuals showed a more lenient criterion in judging the lexicality of the items, a tendency that may explain why, despite lower accuracy, they were not slower. It is concluded that binary tasks (and the Diffusion model) can reveal cross-linguistic differences in orthographic processing which would otherwise be difficult to detect in standard single-word reading tasks.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Association patterns and community structure among female bottlenose dolphins: environmental, genetic and cultural factors - Svenja M. Marfurt; Simon J. Allen; Manuela R. Bizzozzero; Erik P. Willems; Stephanie L. King; Richard C. Connor; Anna M. Kopps; Sonja Wild; Livia Gerber; Samuel Wittwer; Michael Krützen (Mammalian Biology, 2022)
Social structuring from assortative associations may affect individual fitness, as well as population-level processes. Gaining a broader understanding of social structure can improve our knowledge of social evolution and inform wildlife conservation. We investigated association patterns and community structure of female Indo-Pacific bottlenose dolphins ( Tursiops aduncus ) in Shark Bay, Western Australia, assessing the role of kinship, shared culturally transmitted foraging techniques, and habitat similarity based on water depth. Our results indicated that associations are influenced by a combination of uni- and biparental relatedness, cultural behaviour and habitat similarity, as these were positively correlated with a measure of dyadic association. These findings were matched in a community level analysis. Members of the same communities overwhelmingly shared the same habitat and foraging techniques, demonstrating a strong homophilic tendency. Both uni- and biparental relatedness between dyads were higher within than between communities. Our results illustrate that intraspecific variation in sociality in bottlenose dolphins is influenced by a complex combination of genetic, cultural, and environmental aspects.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Oystershell scale: an emerging invasive threat to aspen in the southwestern US - Connor D. Crouch; Amanda M. Grady; Nicholas P. Wilhelmi; Richard W. Hofstetter; Daniel E. DePinte; Kristen M. Waring (Biological Invasions, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

The effects of normoxic endurance exercise on erythropoietin (EPO) production and the impact of selective β1 and non-selective β1 + β2 adrenergic receptor blockade - Rod J. Azadan; Nadia H. Agha; Hawley E. Kunz; Forrest L. Baker; Preteesh L. Mylabathula; Tracy A. Ledoux; Daniel P. O’Connor; Charles R. Pedlar; Richard J. Simpson (European Journal of Applied Physiology, 2021)

Pediatric Methamphetamine Toxicity: Clinical Manifestations and Therapeutic Use of Antipsychotics—One Institution’s Experience - Hannah R. Malashock; Claudia Yeung; Alexa R. Roberts; Jerry W. Snow; Richard D. Gerkin; Ayrn D. O’Connor (Journal of Medical Toxicology, 2021)

Potential late effects of SARS-CoV-2 (COVID-19) infection: parallels to cancer late effects - Richard P. Phipps; Patricia J. Sime; Connor R. Phipps (Cancer and Metastasis Reviews, 2021)

Sensor Anchoring Improves the Correlation Between Intramuscular Pressure and Muscle Tension in a Rabbit Model - Shawn M. O’Connor; Kenton R. Kaufman; Samuel R. Ward; Richard L. Lieber (Annals of Biomedical Engineering, 2021)

Sherri Eldridge 1959–2020 - Richard C. Connor; Darlene R. Ketten; Michael J. Moore; Joy S. Reidenberg; Douglas L. Rosene; Tammy Silva; David N. Wiley (Marine Mammal Science, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Association between Urinary Metabolite Levels of Organophosphorus Flame Retardants and Serum Sex Hormone Levels Measured in a Reference Sample of the US General Population - Binnian Wei; Richard O’Connor; Maciej Goniewicz; Andrew Hyland (Exposure and Health, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Effect of e-cigarette flavors on nicotine delivery and puffing topography: results from a randomized clinical trial of daily smokers - Natalie Voos; Danielle Smith; Lisa Kaiser; Martin C. Mahoney; Clara M. Bradizza; Lynn T. Kozlowski; Neal L. Benowitz; Richard J. O’Connor; Maciej L. Goniewicz (Psychopharmacology, 2020)

Atlantic salmon Salmo salar passing a natural barrier before and after construction of a hydroelectric station - Richard James Kennedy; William O'Connor; Michelle Allen (Journal of Fish Biology, 2019)
A hydro power plant constructed around a waterfall on a coastal spate river, used the fall as a natural fish pass and applied a previous telemetry study on local Atlantic salmon Salmo salar to determine the abstraction conditions for the site. The current study used the same telemetry approach to monitor the efficacy of S. salar passage and to compare migratory behaviour at the waterfall pre and post the hydro development. The probability of S. salar successfully crossing the waterfall was higher post‐hydro when 80% of tagged fish successfully crossed in comparison to the pristine pre‐hydro period when 44% of tagged fish ascended. The flow range used by tagged S. salar to cross the waterfall ranged from 2.49−7.87 m 3 s −1 in the pre‐hydro period but broadened to 1.32−12.91 m 3 s −1 during the post‐hydro period. This was principally due to the hydro diverting water away from the waterfall during spate conditions, damping the flow across the barrier and facilitating upstream migration within a more suitable discharge range. During 2017–2018 implementation of the hydro‐operation protocol elongated the duration of the migratory window for successful upstream migration by 36–128%. A strong diurnal pattern was observed for movements across the Salmon Leap waterfall during both the pre‐hydro and post‐hydro monitoring periods with most tagged S. salar crossing the complex obstacle in daylight.

Male aggression varies with consortship rate and habitat in a dolphin social network - Rebecca A. Hamilton; Teresa Borcuch; Simon J. Allen; William R. Cioffi; Vanni Bucci; Michael Krützen; Richard C. Connor (Behavioral Ecology and Sociobiology, 2019)

Loving the mess: navigating diversity and conflict in social values for sustainability - Jasper O. Kenter; Christopher M. Raymond; Carena J. van Riper; Elaine Azzopardi; Michelle R. Brear; Fulvia Calcagni; Ian Christie; Michael Christie; Anne Fordham; Rachelle K. Gould; Christopher D. Ives; Adam P. Hejnowicz; et al. (Sustainability Science, 2019)

Focus Groups and In-depth Interviews to Guide the Development of Lung Cancer Screening Informational Materials - Anushree Sharma; Richard O’Connor; Paula Celestino; Samantha Killion; Laurie Griswold-Krupski; Maansi Bansal-Travers (Journal of Cancer Education, 2019)

The Relationship Between Circulating Acetaminophen-Protein Adduct Concentrations and Alanine Aminotransferase Activities in Patients With and Without Acetaminophen Overdose and Toxicity - Steven C. Curry; Angela Padilla-Jones; Anne-Michelle Ruha; Ayrn D. O’Connor; A Min Kang; Diana G. Wilkins; Hartmut Jaeschke; Kelly Wilhelms; Richard D. Gerkin (Journal of Medical Toxicology, 2019)

Awareness and interest in lung cancer screening among current and former smokers: findings from the ITC United States Survey - Anushree Sharma; Karin Kasza; Andrew Hyland; K. Michael Cummings; Maansi Bansal-Travers; Geoffrey T. Fong; Richard J. O’Connor (Cancer Causes & Control, 2019)

Discovery of new code interference phenomenon in GPS observables - Connor D. Flynn; Anthony M. McCaffrey; P. T. Jayachandran; Richard B. Langley (GPS Solutions, 2019)

Increased amygdalar metabotropic glutamate receptor 7 mRNA in a genetic mouse model of impaired fear extinction - Richard M. O’Connor; Cian P. McCafferty; Javier A. Bravo; Nicolas Singewald; Andrew Holmes; John F. Cryan (Psychopharmacology, 2019)

Role of inositol polyphosphates in programed cell death in Dictyostelium discoideum and its developmental life cycle - Qudes Al-Anbaky; Zeiyad Al-karakooly; Richard Connor; Lisa Williams; Azure Yarbrough; John Bush; Nawab Ali (Molecular and Cellular Biochemistry, 2018)

Mātauranga Māori driving innovation in the New Zealand scampi fishery - Shaun Ogilvie; Robert Major; Alaric McCarthy; Glenice Paine; Richard Paine; Geoff Connor; Steve Connor; David Taylor; Andrew Jeffs; Kevin Heasman; Chris Batstone; Benita Chambers; et al. (New Zealand Journal of Marine and Freshwater Research, 2018)
Motivation to improve commercial fishing technology is changing from ‘how can we catch more fish’ to ‘how can we reduce the impact of fishing on the environment’. To implement new fisheries technologies and innovations, it is important to have sources of innovative ideas for improvement, and processes to allow the uptake and transition from old to new technologies. One fishery that is undergoing a technology transition is the New Zealand scampi ( Metanephrops challengeri ) fishery. Here we report on a research programme aimed at improving the cultural and environmental performance of scampi fishing practices, initiated by the Māori‐owned Waikawa Fishing Company, and underpinned by Mātauranga Māori and values inherent in kaitiakitanga. This paper provides a case study for how Mātauranga Māori and western science can engage in a fisheries technology transition through a transdisciplinary research programme.

Sensory neuropathic symptoms in idiopathic Parkinson’s disease: prevalence and impact on quality of life - Joy K. Adewusi; Marios Hadjivassiliou; Ana Vinagre-Aragón; Karen Ruth O’Connor; Aijaz Khan; Richard Adam Grünewald; Panagiotis Zis (Acta Neurologica Belgica, 2018)

Social reinforcement as alternative to sucrose reinforcement is increased by nicotine and methylphenidate in male Fischer-344 rats - Connor D. Martin; Heather M. Bool; Anthony M. George; Katelyn A. Carr; Leonard H. Epstein; Larry W. Hawk; Jerry B. Richards (Psychopharmacology, 2018)

Niche opportunities for invasive annual plants in dryland ecosystems are controlled by disturbance, trophic interactions, and rainfall - Richard A. Gill; Rory C. O’Connor; Aaron Rhodes; Tara B. B. Bishop; Daniel C. Laughlin; Samuel B. St. Clair (Oecologia, 2018)

Latitude, temperature, and habitat complexity predict predation pressure in eelgrass beds across the Northern Hemisphere - Pamela L. Reynolds; John J. Stachowicz; Kevin Hovel; Christoffer Boström; Katharyn Boyer; Mathieu Cusson; Johan S. Eklöf; Friederike G. Engel; Aschwin H. Engelen; Britas Klemens Eriksson; F. Joel Fodrie; John N. Griffin; et al. (Ecology, 2018)
Latitudinal gradients in species interactions are widely cited as potential causes or consequences of global patterns of biodiversity. However, mechanistic studies documenting changes in interactions across broad geographic ranges are limited. We surveyed predation intensity on common prey (live amphipods and gastropods) in communities of eelgrass ( Zostera marina ) at 48 sites across its Northern Hemisphere range, encompassing over 37° of latitude and four continental coastlines. Predation on amphipods declined with latitude on all coasts but declined more strongly along western ocean margins where temperature gradients are steeper. Whereas in situ water temperature at the time of the experiments was uncorrelated with predation, mean annual temperature strongly positively predicted predation, suggesting a more complex mechanism than simply increased metabolic activity at the time of predation. This large‐scale biogeographic pattern was modified by local habitat characteristics; predation declined with higher shoot density both among and within sites. Predation rates on gastropods, by contrast, were uniformly low and varied little among sites. The high replication and geographic extent of our study not only provides additional evidence to support biogeographic variation in predation intensity, but also insight into the mechanisms that relate temperature and biogeographic gradients in species interactions.

Improved full-length killer cell immunoglobulin-like receptor transcript discovery in Mauritian cynomolgus macaques - Trent M. Prall; Michael E. Graham; Julie A. Karl; Roger W. Wiseman; Adam J. Ericsen; Muthuswamy Raveendran; R. Alan Harris; Donna M. Muzny; Richard A. Gibbs; Jeffrey Rogers; David H. O’Connor (Immunogenetics, 2017)

Evaluation of Non-destructive Molecular Diagnostics for the Detection of Neoparamoeba perurans - Jamie K. Downes; Megan L. Rigby; Richard S. Taylor; Ben T. Maynard; Eugene MacCarthy; Ian O'Connor; Mar Marcos-Lopez; Hamish D. Rodger; Evelyn Collins; Neil M. Ruane; Mathew T. Cook (Frontiers in Marine Science, 2017)

Design Considerations of a Fiber Optic Pressure Sensor Protective Housing for Intramuscular Pressure Measurements - Shanette A. Go; Elisabeth R. Jensen; Shawn M. O’Connor; Loribeth Q. Evertz; Duane A. Morrow; Samuel R. Ward; Richard L. Lieber; Kenton R. Kaufman (Annals of Biomedical Engineering, 2017)

Louis M. Herman 1930–2016 - Adam A. Pack; Elia Y. K. Herman; C. Scott Baker; Gordon B. Bauer; Phillip J. Clapham; Richard C. Connor; Alison S. Craig; Paul H. Forestell; Adam S. Frankel; Giuseppe Notarbartolo di Sciara; Matthias Hoffmann‐Kuhnt; Eduardo Mercado; et al. (Marine Mammal Science, 2017)

Biotic resistance and disturbance: rodent consumers regulate post‐fire plant invasions and increase plant community diversity - Samuel B. St. Clair; Rory O'Connor; Richard Gill; Brock McMillan (Ecology, 2016)
Biotic resistance and disturbance are fundamental processes influencing plant invasion outcomes; however, the role of consumers in regulating the establishment and spread of plant invaders and how disturbance modifies biotic resistance by consumers is unclear. We document that fire in combination with experimental exclusion of rodent consumers shifted a native desert shrubland to a low‐diversity, invasive annual grassland dominated by Bromus tectorum (cheatgrass). In contrast, burned plots with rodents present suppressed invasion by cheatgrass and developed into a more diverse forb community. Rodents created strong biotic resistance to the establishment of aggressive plant invaders likely through seed and seedling predation, which had cascading effects on plant competition and plant community diversity. Fire mediated its positive effects on plant invaders through native plant removal and by decreasing the abundance and diversity of the rodent community. The experimental disruption of plant and consumer‐mediated biotic resistance of plant invaders using fire and rodent exclusion treatments provides strong evidence that native plants and rodents are important regulators of plant invasion dynamics and plant biodiversity in our study system. While rodents conferred strong resistance to invasion in our study system, fluctuations in rodent populations due to disturbance and climatic events may provide windows of opportunity for exotic plant species to escape biotic resistance by rodent consumers and initiate invasions.

Persistence and amplitude of cigarette demand in relation to quit intentions and attempts - Richard J. O’Connor; Bryan W. Heckman; Sarah E. Adkison; Vaughan W. Rees; Dorothy K. Hatsukami; Warren K. Bickel; K. Michael Cummings (Psychopharmacology, 2016)

Comparison of Prothrombin Time and Aspartate Aminotransferase in Predicting Hepatotoxicity After Acetaminophen Overdose: a Response - Michael Levine; Ayrn D. O’Connor; Angela Padilla-Jones; Richard Gerkin (Journal of Medical Toxicology, 2016)

Advancing Product Quality: a Summary of the Second FDA/PQRI Conference - Lawrence X. Yu; Ilgaz Akseli; Barbara Allen; Gregory Amidon; Tara Gooen Bizjak; Ashley Boam; Margaret Caulk; David Doleski; Joseph Famulare; Adam C. Fisher; Scott Furness; Brian Hasselbalch; et al. (The AAPS Journal, 2016)

Comparison of Prothrombin Time and Aspartate Aminotransferase in Predicting Hepatotoxicity After Acetaminophen Overdose - Michael Levine; Ayrn D. O’Connor; Angela Padilla-Jones; Richard D. Gerkin (Journal of Medical Toxicology, 2016)

Obesity, ethnicity, and quality of life among breast cancer survivors and women without breast cancer: the long-term quality of life follow-up study - Avonne E. Connor; Richard N. Baumgartner; Christina M. Pinkston; Stephanie D. Boone; Kathy B. Baumgartner (Cancer Causes & Control, 2016)

Group size and feeding success in strand‐feeding bottlenose dolphins ( Tursiops truncatus ) in Bull Creek, South Carolina - Teresa J. Gisburne; Richard C. Connor (Marine Mammal Science, 2015)

Prevalence of Rhabdomyolysis in Sympathomimetic Toxicity: a Comparison of Stimulants - Ayrn D. O’Connor; Angie Padilla-Jones; Richard D. Gerkin; Michael Levine (Journal of Medical Toxicology, 2015)

Prolonged Acetaminophen-Protein Adduct Elimination During Renal Failure, Lack of Adduct Removal by Hemodiafiltration, and Urinary Adduct Concentrations After Acetaminophen Overdose - Steven C. Curry; Angela Padilla-Jones; Ayrn D. O’Connor; Anne-Michelle Ruha; Dale S. Bikin; Diana G. Wilkins; Douglas E. Rollins; Matthew H. Slawson; Richard D. Gerkin (Journal of Medical Toxicology, 2015)

Effect of risk aversion on prioritizing conservation projects - Ayesha I.T. Tulloch; Richard F. Maloney; Liana N. Joseph; Joseph R. Bennett; Martina M.I. Di Fonzo; William J.M. Probert; Shaun M. O'Connor; Jodie P. Densem; Hugh P. Possingham (Conservation Biology, 2015)
Conservation outcomes are uncertain. Agencies making decisions about what threat mitigation actions to take to save which species frequently face the dilemma of whether to invest in actions with high probability of success and guaranteed benefits or to choose projects with a greater risk of failure that might provide higher benefits if they succeed. The answer to this dilemma lies in the decision maker's aversion to risk—their unwillingness to accept uncertain outcomes. Little guidance exists on how risk preferences affect conservation investment priorities. Using a prioritization approach based on cost effectiveness, we compared 2 approaches: a conservative probability threshold approach that excludes investment in projects with a risk of management failure greater than a fixed level, and a variance‐discounting heuristic used in economics that explicitly accounts for risk tolerance and the probabilities of management success and failure. We applied both approaches to prioritizing projects for 700 of New Zealand's threatened species across 8303 management actions. Both decision makers’ risk tolerance and our choice of approach to dealing with risk preferences drove the prioritization solution (i.e., the species selected for management). Use of a probability threshold minimized uncertainty, but more expensive projects were selected than with variance discounting, which maximized expected benefits by selecting the management of species with higher extinction risk and higher conservation value. Explicitly incorporating risk preferences within the decision making process reduced the number of species expected to be safe from extinction because lower risk tolerance resulted in more species being excluded from management, but the approach allowed decision makers to choose a level of acceptable risk that fit with their ability to accommodate failure. We argue for transparency in risk tolerance and recommend that decision makers accept risk in an adaptive management framework to maximize benefits and avoid potential extinctions due to inefficient allocation of limited resources. El Efecto de la Aversión de Riesgo sobre la Priorización de Proyectos de Conservación

Managing Bay and Estuarine Ecosystems for Multiple Services - Lisa A. Needles; Sarah E. Lester; Richard Ambrose; Anders Andren; Marc Beyeler; Michael S. Connor; James E. Eckman; Barry A. Costa-Pierce; Steven D. Gaines; Kevin D. Lafferty; Hunter S. Lenihan; Julia Parrish; et al. (Estuaries and Coasts, 2015)

Associations between CYP19A1 polymorphisms, Native American ancestry, and breast cancer risk and mortality: the Breast Cancer Health Disparities Study - Stephanie D. Boone; Kathy B. Baumgartner; Richard N. Baumgartner; Avonne E. Connor; Christina M. Pinkston; Shesh N. Rai; Elizabeth C. Riley; Lisa M. Hines; Anna R. Giuliano; Esther M. John; Mariana C. Stern; Gabriela Torres-Mejía; et al. (Cancer Causes & Control, 2014)

Novel tools for characterising inter and intra chromosomal rearrangements in avian microchromosomes - Pamela E Lithgow; Rebecca O’Connor; Deborah Smith; Gothami Fonseka; Abdullah Al Mutery; Claudia Rathje; Richard Frodsham; Patricia O’Brien; Fumio Kasai; Malcolm A. Ferguson-Smith; Benjamin M. Skinner; Darren K. Griffin (Chromosome Research, 2014)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

ADRB2 G–G haplotype associated with breast cancer risk among Hispanic and non-Hispanic white women: interaction with type 2 diabetes and obesity - Avonne Connor; Richard N. Baumgartner; Richard A. Kerber; Elizabeth O’Brien; Shesh N. Rai; Roger K. Wolff; Martha L. Slattery; Anna R. Giuliano; Betsy C. Risendal; Tim E. Byers; Kathy B. Baumgartner (Cancer Causes & Control, 2012)

The role of MHC class I allele Mamu-A*07 during SIVmac239 infection - Jason S. Reed; John Sidney; Shari M. Piaskowski; Chrystal E. Glidden; Enrique J. León; Benjamin J. Burwitz; Holly L. Kolar; Christopher M. Eernisse; Jessica R. Furlott; Nicholas J. Maness; Andrew D. Walsh; Richard A. Rudersdorf; et al. (Immunogenetics, 2011)

Shotgun Proteomic Analysis of Emiliania huxleyi, a Marine Phytoplankton Species of Major Biogeochemical Importance - Bethan M. Jones; Richard J. Edwards; Paul J. Skipp; C. David O’Connor; M. Debora Iglesias-Rodriguez (Marine Biotechnology, 2011)

The impact of acute strenuous exercise on TLR2, TLR4 and HLA.DR expression on human blood monocytes induced by autologous serum - Stephen Booth; Geraint D. Florida-James; Brian K. McFarlin; Guillaume Spielmann; Daniel P. O’Connor; Richard J. Simpson (European Journal of Applied Physiology, 2010)

Interaction between organochlorines and the AHR gene, and risk of non-Hodgkin lymphoma - Carmen H. Ng; Rozmin Janoo-Gilani; Payal Sipahimalani; Richard P. Gallagher; Randy D. Gascoyne; Joseph M. Connors; Jean-Philippe Weber; Agnes S. Lai; Stephen Leach; Nhu D. Le; Angela R. Brooks-Wilson; John J. Spinelli (Cancer Causes & Control, 2010)

Quantifying a dynamic risk landscape: heterogeneous predator activity and implications for prey persistence - Eric M. Schauber; Matthew J. Connors; Brett J. Goodwin; Clive G. Jones; Richard S. Ostfeld (Ecology, 2009)
Spatial heterogeneity in predation risk can ameliorate impacts on prey populations, particularly for prey of generalists. Spatially heterogeneous risk implies the existence of refugia, and the spatial scale of those refugia and their persistence over time affect whether prey can avoid predation by aggregating therein. Our objective was to quantify the magnitude, spatial scale, and temporal persistence of heterogeneity in risk of predation by white‐footed mice ( Peromyscus leucopus ), an abundant generalist predator of gypsy moths ( Lymantria dispar ) and songbirds. We used track plates to measure white‐footed mouse activity at >170 trees in each of three forest plots in upstate New York during summers of 2003–2005. We quantified the mean and coefficient of variation of track activity among trees by fitting the beta‐binomial distribution to data from each plot and study period. We measured temporal persistence by disattenuated autocorrelation, and spatial scale by fitting exponential variograms. Mice were much less abundant in 2005 than the other two years, leading to lower overall track activity but higher coefficient of variation among trees. Mouse track activity at individual trees was positively autocorrelated between monthly study periods in 2003 and 2004, and even between the two years, whereas temporal autocorrelation in 2005 was much weaker. Track activity showed positive spatial autocorrelation over lag distances from ∼30 to >1000 m. These findings indicate that mouse activity, and hence risk to their prey, varies substantially in space at spatial and temporal scales that appear responsive to mouse population dynamics. The spatial scale and temporal persistence of that variation imply that prey may benefit from returning to, or failing to disperse from, refugia.

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Quetiapine augmentation of paroxetine CR for the treatment of refractory generalized anxiety disorder: preliminary findings - Naomi M. Simon; Kathryn M. Connor; Richard T. LeBeau; Elizabeth A. Hoge; John J. Worthington; Wei Zhang; Jonathan R. T. Davidson; Mark H. Pollack (Psychopharmacology, 2008)

Observations of strand‐feeding behavior by bottlenose dolphins ( Tursiops truncatus ) in Bull Creek, South Carolina - Erin E. Duffy‐Echevarria; Richard C. Connor; David J. St. Aubin (Marine Mammal Science, 2008)

A PRELIMINARY EXAMINATION OF SEX DIFFERENCES IN TACTILE INTERACTIONS AMONG JUVENILE ATLANTIC SPOTTED DOLPHINS ( STENELLA FRONTALIS ) - J. Daisy Kaplan; Richard C. Connor (Marine Mammal Science, 2007)

Decline in Relative Abundance of Bottlenose Dolphins Exposed to Long‐Term Disturbance - LARS BEJDER; AMY SAMUELS; HAL WHITEHEAD; NICK GALES; JANET MANN; RICHARD CONNOR; MIKE HEITHAUS; JANA WATSON‐CAPPS; CINDY FLAHERTY; MICHAEL KRÜTZEN (Conservation Biology, 2006)
Studies evaluating effects of human activity on wildlife typically emphasize short‐term behavioral responses from which it is difficult to infer biological significance or formulate plans to mitigate harmful impacts. Based on decades of detailed behavioral records, we evaluated long‐term impacts of vessel activity on bottlenose dolphins ( Tursiops sp.) in Shark Bay, Australia. We compared dolphin abundance within adjacent 36‐km 2 tourism and control sites, over three consecutive 4.5‐year periods wherein research activity was relatively constant but tourism levels increased from zero, to one, to two dolphin‐watching operators. A nonlinear logistic model demonstrated that there was no difference in dolphin abundance between periods with no tourism and periods in which one operator offered tours. As the number of tour operators increased to two, there was a significant average decline in dolphin abundance (14.9%; 95% CI =−20.8 to −8.23), approximating a decline of one per seven individuals. Concurrently, within the control site, the average increase in dolphin abundance was not significant (8.5%; 95% CI =−4.0 to +16.7). Given the substantially greater presence and proximity of tour vessels to dolphins relative to research vessels, tour‐vessel activity contributed more to declining dolphin numbers within the tourism site than research vessels. Although this trend may not jeopardize the large, genetically diverse dolphin population of Shark Bay, the decline is unlikely to be sustainable for local dolphin tourism. A similar decline would be devastating for small, closed, resident, or endangered cetacean populations. The substantial effect of tour vessels on dolphin abundance in a region of low‐level tourism calls into question the presumption that dolphin‐watching tourism is benign.

Spatial Relationships Between Water Quality and Pesticide Application Rates in Agricultural Watersheds - John W. Hunt; Brian S. Anderson; Bryn M. Phillips; Ron S. Tjeerdema; Nancy Richard; Val Connor; Karen Worcester; Mark Angelo; Amanda Bern; Brian Fulfrost; Dustin Mulvaney (Environmental Monitoring and Assessment, 2006)

Tiagabine for posttraumatic stress disorder: effects of open-label and double-blind discontinuation treatment - Kathryn M. Connor; Jonathan R. T. Davidson; Richard H. Weisler; Wei Zhang; Kurian Abraham (Psychopharmacology, 2006)

Causes of tail fan necrosis in the southern rock lobster, Jasus edwardsii - Richard J. Musgrove; Michael C. Geddes; Connor Thomas (New Zealand Journal of Marine and Freshwater Research, 2005)
Tail fan necrosis (TFN) is a recognised constraint on the advancement of the South Australian rock lobster (Jasus edwardsii) liveholding industry because of a reduction in value of afflicted lobsters. Trials were run in the laboratory and at a shore‐based experimental live‐holding facility (LHF) to determine the influence of at‐sea post‐harvest handling, feeding frequency (LHF only), density (LHF only), and temperature (laboratory only) on the advent of the condition. Lobsters were caught during normal fishing operations and either immediately placed in protective fine‐mesh nylon bags and stored in the boat's well or placed unbagged in the well. At the laboratory, the tail fans of half the bagged lobsters were deliberately damaged with sterile instruments. At the LHF the TFN level increased significantly over 4 months. The bagged treatment showed significantly less late‐stage TFN than unbagged daily or weekly‐fed treatments with 60% of bagged lobsters showing no TFN at 4 months. With unbagged lobsters, 50% showed erosion in the 25% of the tail fan. Lobster density and feeding frequency had no effect on TFN incidence. In the laboratory, bagged and bagged‐damaged treatments had no advanced TFN after the 6‐week period suggesting that post‐harvest bagging minimises TFN and that inflicting physical damage to lobster tail fans with aseptic instruments does not lead to its development. Temperature had no effect on TFN development. The highest incidence of TFN was found in lobsters given normal post‐harvest handling, that is, communal holding in boat holds and tanks (i.e., without bags). These conditions are normally associated with physical damage inflicted by conspecifics. Such damage will presumably also involve infection of wounds by the bacterial flora of the crayfish exoskeleton, leading to development of TFN.

‘O father: where art thou?’— Paternity assessment in an open fission–fusion society of wild bottlenose dolphins ( Tursiops sp.) in Shark Bay, Western Australia - Michael Krützen; Lynne M. Barré; Richard C. Connor; Janet Mann; William B. Sherwin (Molecular Ecology, 2004)
Sexually mature male bottlenose dolphins in Shark Bay cooperate by pursuing distinct alliance strategies to monopolize females in reproductive condition. We present the results of a comprehensive study in a wild cetacean population to test whether male alliance membership is a prerequisite for reproductive success. We compared two methods for inferring paternity: both calculate a likelihood ratio, called the paternity index, between two opposing hypotheses, but they differ in the way that significance is applied to the data. The first method, a Bayesian approach commonly used in human paternity testing, appeared to be overly conservative for our data set, but would be less susceptible to assumptions if a larger number of microsatellite loci had been used. Using the second approach, the computer program cervus 2.0, we successfully assigned 11 paternities to nine males, and 17 paternities to 14 out of 139 sexually mature males at 95% and 80% confidence levels, respectively. It appears that being a member of a bottlenose dolphin alliance is not a prerequisite for paternity: two paternities were obtained by juvenile males (one at the 95%, the other at the 80% confidence level), suggesting that young males without alliance partners pursue different mating tactics to adults. Likelihood analyses showed that these two juvenile males were significantly more likely to be the true father of the offspring than to be their half‐sibling ( P P P

RESTRUCTURING DYNAMICS OF DU 145 AND LNCaP PROSTATE CANCER SPHEROIDS - HONG SONG; SHAMIK K. JAIN; RICHARD M. ENMON; KIM C. O'CONNOR (In Vitro Cellular & Developmental Biology - Animal, 2004)

Restructuring Dynamics of DU 145 and LNCaP Prostate Cancer Spheroids - Hong Song; Shamik K. Jain; Richard M. Enmon; Kim C. O'Connor (In Vitro Cellular & Developmental Biology - Animal, 2003)

Forest Stewardship Council Forest Certification - Henry A. Cauley; Charles M. Peters; Richard Z. Donovan; Jennifer M. O'Connor (Conservation Biology, 2001)

P redation P ast and P resent : - Richard C. Connor; Peter J. Corkeron (Marine Mammal Science, 2001)

“KERPLUNKING”: SURFACE FLUKE‐SPLASHES DURING SHALLOW‐WATER BOTTOM FORAGING BY BOTTLENOSE DOLPHINS - Richard C. Connor; Michael R. Heithaus; Per Berggren; Jennifer L. Miksis (Marine Mammal Science, 2000)

RECOLLECTIONS OF AN UNDERGRADUATE NORRIS GROUPIE - Richard Connor (Marine Mammal Science, 1999)

WHY DO BALEEN WHALES MIGRATE? 1 - Peter J. Corkeron; Richard C. Connor (Marine Mammal Science, 1999)
A bstract The annual migrations of baleen whales are a conspicuous but unexplained feature of their behavioral repertoire. Some hypotheses offered to explain whale migration focus on direct benefits to the calf (thermoregulation, calm water) and some do not (resource tracking, and the “evolutionary holdover” hypothesis). Here, we suggest that a major selective advantage to migrating pregnant female baleen whales is a reduced risk of killer whale ( Orcinus orca ) predation on their newborn calves in low‐latitude waters. Killer whale abundance in high latitudes is substantially greater than that in lower latitudes, and most killer whales do not appear to migrate with baleen whales. We suggest that the distribution of killer whales is determined more by their primary marine mammal prey, pinnipeds, and that following the baleen whale migrations would remove them from their pinniped prey. There are problems with all current hypotheses, most of which stem from a lack of directed research. We explore variation in migratory habits between species, populations, and individuals that may provide a “natural laboratory” for discriminating among the competing hypotheses.

The biological response of MCF7 breast cancer cells to proteosome inhibition or γ-radiation is unrelated to the level of p53 induction - L. H. Fallis; E. Richards; D. J. O'Connor; S. Zhong; J. K. Hsieh; G. Packham; X. Lu (Apoptosis, 1999)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Landfill leachate: A study of its anaerobic mineralization and toxicity to methanogenesis - Owen A. O'Connor; Richard Dewan; Paul Galuzzi; L. Y. Young (Archives of Environmental Contamination and Toxicology, 1990)